Human papillomavirus vaccination hesitancy among young girls in Ethiopia: factors and barriers to uptake - Ashenafi Kibret Sendekie; Ashenafi Kibret Sendekie; Biruk Beletew Abate; Biruk Beletew Abate; Betelhem Anteneh Adamu; Aschalew Mulatu Tefera; Kaleab Temelket Mekonnen; Melkam Alemu Ashagrie; Yabibal Berie Tadesse; Abera Dessie Dagnaw; Mequannent Sharew Melaku; Gizachew Kassahun Bizuneh (Frontiers in Public Health)
BackgroundHuman papillomavirus (HPV) vaccinations protect against HPV infections. The infection might lead to vaginal cancer, vulvar cancer, genital warts, cervical intraepithelial neoplasia lesions, and cervical cancer. This study assessed hesitancy of HPV vaccination, associated factors, and barriers to vaccination among youth girls in Ethiopia.MethodsAn institutional-based cross-sectional study was conducted among female undergraduate students at the University of Gondar, College of Medicine and Health Sciences, between July and August 2022. The data was collected using a self-administered questionnaire. A simple random sampling method was used to recruit participants. The data were entered and analyzed with SPSS version 26. Descriptive statistics were used to describe the participants’ demographic characteristics. Logistic regression was performed to identify the significant factors associated with acceptance of the HPV vaccine. A p-value <0.05 was considered statistically significant.ResultsThe study included 423 participants with a mean age of 22.5 ± 6.7 years. Only more than one-third (35.2, 95% CI: 27.2–44.1) received the HPV vaccine. Currently, more than one-fourth (27.9, 95% Cl: 21.4–33.8) of participants are hesitant to receive the HPV vaccine. Higher monthly income (AOR = 1.52, 95% CI: 1.08–6.34), good knowledge of the HPV vaccine (AOR = 2.12, 95% CI: 1.12–4.87), and a positive attitude towards the vaccine (AOR = 3.03, 95% CI: 1.63–9.56) were significantly associated with acceptance of HPV vaccination. Safety concerns (63.1%), misinformation (42.8%), and parental concerns (42.3%) about the HPV vaccine were among the top perceived reported barriers to receiving the HPV vaccine.ConclusionThis result showed that more than a quarter number of youth girls are still hesitant to receive HPV vaccinations. To increase vaccination acceptance, interventions should focus on awareness-raising programs about HPV infection and vaccines and addressing safety and parental concerns.